2017
DOI: 10.1093/mnras/stx558
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical lifetimes of asteroids in retrograde orbits

Abstract: The population of known minor bodies in retrograde orbits (i > 90 • ) that are classified as asteroids is still growing. The aim of our study was to estimate the dynamical lifetimes of these bodies by use of the latest observational data, including astrometry and physical properties. We selected 25 asteroids with the best determined orbital elements. We studied their dynamical evolution in the past and future for ± 100 My (± 1 Gy for three particular cases).We first used orbit determination and cloning to prod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…de la Fuente Marcos & de la Fuente Marcos (2014) analyzed the dynamical evolutions of the 3 large retrograde centaurs (2008YB3, 2011MM4, and 2013. Kankiewicz & Włodarczyk (2017 studied the dynamical lifetimes of the 25 selected retrograde asteroids. They found that retrograde asteroids are generally unstable, and most of the retrograde asteroids have short life spans (<1 Myr).…”
Section: Dynamical Lifetimes Of Retrograde Asteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…de la Fuente Marcos & de la Fuente Marcos (2014) analyzed the dynamical evolutions of the 3 large retrograde centaurs (2008YB3, 2011MM4, and 2013. Kankiewicz & Włodarczyk (2017 studied the dynamical lifetimes of the 25 selected retrograde asteroids. They found that retrograde asteroids are generally unstable, and most of the retrograde asteroids have short life spans (<1 Myr).…”
Section: Dynamical Lifetimes Of Retrograde Asteroidsmentioning
confidence: 99%
“…Our results provide a systematic survey for the research on related topics. Kankiewicz & Włodarczyk (2017 studied dynamical lifetimes of 25 retrograde asteroids. Generally speaking, the dynamical lifetimes of the selected bodies are shorter than those of most prograde asteroids in the solar system.…”
Section: Introductionmentioning
confidence: 99%
“…Our first estimation of τ values for retrograde orbits is described in detail in Kankiewicz & Włodarczyk (2017). In this study, we found that this parameter is sensitive to relatively weak non-gravitational forces, such as the Yarkovsky effect.…”
Section: Introductionmentioning
confidence: 62%
“…This fact influenced the method we chose. Because previously (Kankiewicz & Włodarczyk 2017) we obtained relatively short dynamical lifetimes of retrograde asteroids (on the order of millions of years), these orbits can be suspected to be more chaotic than most small bodies. Our procedure for the numerical calculation of LCI was based on methods originally introduced by Benettin et al (1976), adapted and described in detail by Murray & Dermott (2000) and Sprott (2003).…”
Section: Lyapunov Times Estimationmentioning
confidence: 92%
“…1). In our recent study (Kankiewicz & Włodarczyk 2017), we analysed the dynamical lifetimes of the same asteroid group (not including 6 asteroids added later to this paper after the update of observational data). All of the objects from this list were classified as either Centaurs, TNOs, or NEAs (only one Apollotype asteroid).…”
Section: Initial Datamentioning
confidence: 99%